GAMBARAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA LANSIA DI UPT PUSKESMAS TUNTUNGAN - Tinah, Tinah; Priska Frisilia Sinaga (Poltekkes Kemenkes Medan, 2024)
The Behavior of Clean and Healthy Living is a form of behavior in daily life that is very important, a factor that supports the creation of a better quality of life. The elderly are a group of people aged over 60 years, experiencing many cell declines that affect their body systems, resulting in disturbances in clean and healthy living behavior. This study aims to get an overview of clean and healthy living behavior in the elderly at the Technical Implementation Unit of the Tuntungan Health Center with indicators: washing hands with soap, eating fruits and vegetables every day, and physical activity every day. This research is a quantitative descriptive study with a cross-sectional design, and examines 84 elderly as samples determined through accidental sampling technique. Through the results of the study it is known that the level of knowledge of the elderly: washing hands with soap is in good criteria; eating fruit and vegetables every day is in good criteria; and daily physical activity is within fair criteria; attitude level of the elderly: washing hands with soap is in good criteria; eating fruit and vegetables every day is in good criteria, and daily physical activity is in fair criteria; actions of the elderly: washing hands with soap is in good criteria, eating fruits and vegetables every day is in good criteria, and daily physical activity is in fair criteria. The conclusion of this study is that some of the elderly have Clean and Healthy Behavior which is in the good category. It is hoped that the elderly will further improve their behavior regarding Clean and Healthy Living by consulting with health workers, visiting the Integrated Health Service Post for the elderly, to improve the physical fitness of the elderly due to lack of physical activity, and families to improve communication with the elderly, especially giving praise, when the elderly able to improve their behavior about clean and healthy living